From molecules to crystallizers - Davey, R.; Garside, John, 1941-; Oxford University Press (Oxford ; New York : Oxford University Press, 2003)
This work examines crystallisation, one of the oldest separation processes used in the chemical industry and still one of the most important.
-- Introduction -- Phase equiliibria and crystallization techniques -- Nucleation -- Crystal growth -- Crystal morphology -- Polymorphism -- Number balances and size distribution modelling -- Characteristics of continuous and batch crystallizers -- Crystals in formulated products
Includes bibliographical references and index.
Keywords: Crystallization